etrital zircon U/Pb ages and provenance study of the Paleocene to Miocene Tofino basin sedimentary sequence, Olympic Peninsula, Washington - Molinek, III Frank Rudolph (Carleton Digital Commons, 2015)
The Tofino basin sedimentary sequence of the northwestern Olympic Peninsula is a Paleocene to Miocene forearc basin that overlies the Crescent terrane and sits adjacent to the Wrangellia. The clastic strata are thought to be derived, at least in part, from the unroofing of the Coast Plutonic Complex (CPC), which is also a primary candidate for the source of the flysch of the Chugach-Prince William Terrane (CPW) in southern Alaska. In this study, samples from the Miocene to Paleocene Blue Mountain, Lyre, Hoko River, and Makah Formations are analyzed for detrital zircon U/Pb ages to compare maximum depositional ages (MDAs) and grain-age population distributions of the Tofino basin to those of correlative CPW. In four of the five samples with reported faunal ages, the U/Pb MDAs are significantly older than the faunal ages, indicating a lack of contemporaneous siliceous volcanism in the source area. Two zircons from the Blue Mountain sample are 48.0 and 50.5 Ma, which may suggest a young basal age for the Crescent Formation of the Olympic Peninsula, and imply a <,1 m.y. time for accumulation of the Crescent Formation. The younger units typically have Eocene populations, and one Makah Formation sample has a Miocene population, most samples also have Late Cretaceous and Jurassic populations. This is different from the contemporaneous Orca Group in the CPW, which typically have large populations from 60 - 50 Ma. However, both are likely sourced from the CPC. Precambrian grains in nearly every sample define peaks at 1.4 Ga, and 1.7 Ga. These are indicative of a potential southern Laurentian source component (Yavapai and Granite - Rhyolite Provinces). This southern Laurentian signature is generally not present in similar age strata in the CPW, but it does occur locally in Alaska.